(untitled) (Baghdad Science Journal, 2024)
Cloud computing is a significant technology model with the strongest potential to change the way IT activities are carried out. The cloud offers low-cost and scalable IT resources. Cloud providers strive to improve business outcomes so cloud systems become more complex. The intelligent cloud has a number of issues, including optimizing the cloud service and designing and distributing resources adaptively and economically. There is a rising trend toward adopting intelligent technologies to better cloud management in particular. This paper introduces an intelligent method to manage cloud resources without delay or trouble. Starting with designing a system based on a genetic algorithm (GA) as a computational tool to achieve the goal and plan a predictive request then depending on the round robin (RR) algorithm to allocate the requests for processing. To evaluate the performance of this method, the proposed algorithm was verified in 145 requests. Where the implementation system achieved a reasonable result.